Reframing tumor bed evaluation in non-small cell lung cancer: histopathological challenges and future directions in the era of neoadjuvant immunotherapy - Pezzuto, Federica; Faccioli, Eleonora; Mnif, Omar El; Maggioni, Giuseppe; Lunardi, Francesca; Fortarezza, Francesco; Giraudo, Chiara; Schiavon, Marco; Bonanno, Laura; Pasello, Giulia; Dell’Amore, Andrea; Calabrese, Fiorella (Frontiers in Oncology, 2026)
The introduction of neoadjuvant immunotherapy in non-small cell lung cancer (NSCLC) has led to complex tumor responses that challenge conventional pathological assessment. Thus, traditional endpoints such as major pathological response (MPR) and pathological complete response (pCR) may become insufficient to capture the full spectrum of immune-mediated changes. Indeed, these parameters were originally developed in the context of cytotoxic chemotherapy and may not reflect immune-mediated phenomena and stromal remodeling which can significantly alter the appearance of the tumor bed. As a result, MPR and pCR may underrepresent the true extent of biological response in patients treated with immunotherapy. This review outlines current limitations in morphologic evaluation and highlights the need for immune-adapted criteria. Furthermore, it explores the additional value of digital pathology and AI that offer objective and reproducible quantification of histologic features. Integrating these tools with radiologic and molecular data supports a multidimensional approach to response assessment, aiming to refine prognostication, guide adjuvant therapy, and ensure consistency in clinical trial designs.